Regularization of the Lagrangian point force approximation for deterministic discrete particle simulations. (August 2019) - Poustis, Jean-François; Senoner, Jean-Mathieu; Zuzio, Davide; Villedieu, Philippe
Highlights: A novel regularization procedure for deterministic Lagrangian point-particle source terms based on the resolution of a nonlinear diffusion equation which allows to locally adapt the regularization length scale while naturally ensuring parallel efficiency. Corrections of the particle's self-induced velocity compatible with the aforementioned novel regularization procedure based on theoretical results of (Maxey and Patel, International Journal of Multiphase Flow, 2001). Demonstration of the compatibility with finite Reynolds number corrections of the particle's self-induced velocity proposed by (Balachandar et al., Journal of Comutational Physics, 2019). A discussion of the interplay between regularization and correction of the particle's self-induced velocity as a compromise between stability and accuracy in the point-particle context. Abstract: The current article presents a regularization procedure of the Lagrangian point-force approach commonly used to account for the perturbation of a fluid phase by a dispersed particle phase. The regularization procedure is based on a nonlinear diffusion equation to naturally ensure parallel efficiency when the regularization length scale extends over several grid cells. The diffusion coefficient thus becomes a function of the particle source term gradient and expressions allowing to approximately adjust the regularization length scale according to the local particle to mesh size ratio are proposed, so that mesh refinement or polydisperse sprays may be handled. Elementary numerical test cases confirm the convergence of the present procedure under mesh refinement and its ability to locally adapt the regularization length scale. Furthermore, the chosen regularization length scale allows to match the leading order term of the perturbation flow field set by the particle beyond approximately two particle diameters in the Stokes regime. When applying the presented source term regularization procedure, the terminal velocity of a particle settling under gravity in the Stokes regime becomes relatively insensitive to mesh refinement. However, errors with respect to the theoretical settling velocity remain substantial and removal of the particle's self induced velocity appears necessary to recover the undisturbed fluid velocity at the particle location and correctly evaluate the drag force. As the current regularization procedure yields source terms that are close to Gaussian, an analytic expression from the literature is used to estimate the particle's self induced velocity. When combining source term regularization and removal of the particle's self induced velocity, good results are obtained for the terminal settling speed in the Stokes regime. Results obtained for horizontally separated particle pairs settling under gravity in the Stokes regime show equally good agreement with theoretical results. Because analytic expressions for the particle's self-induced velocity are no longer available at finite particle Reynolds numbers, correlations recently proposed in the literature are used to obtain correct settling velocities beyond the Stokes regime.